An Experimental Investigation on Photovoltaic Array Power Output Affected by the Different Partial Shading Conditions - Ghoname Abdullah; Hidekazu Nishimura; Toshio Fujita (Energies, 2021)
This paper presents an experimental investigation on photovoltaic array (PV array) power output affected by partial shading conditions (PSCs). An experiment setup of a PV array with a series configuration using 2 <semantics>×</semantics> 4 photovoltaic modules (PV modules) was built. The power output loss due to the shading effect on the first photovoltaic cells (PV cell) connected with bypass diodes of each photovoltaic module, installed in the PV array in the horizontal direction, was evaluated. Depending on the direction of the sun relative to the PV array configuration, the shading percentage was measured during the test and recorded the current and voltage of the PV array. The performance evaluation of the PV array configurations is referred to with respect to the values of maximum power voltage, the maximum power current, maximum power output, power output losses and fill factor (FF). The experimental results show that 44% shading of the first PV cells affects PV array power output loss by more than 80%.